Process for producing phytonutrient enriched diacylglycerols - Baharin, Badlishah Sham; Lo, Seong Koon (2007)
A low cost and more efficient process for producing high-purity phytonutrient-enrinched diacylglycerols is provided by which involves esterifying some or all of the free fatty acids of deodoriser distillates obtained from the processing and refining of edible fats and oils with glycerol. Separation and removal methods are performed to obtain a purified phytonutrient-enriched diacylglycerol product.